Consumer Storytelling of Brand Archetypal Enactments - Muniz, K.; Woodside, Arch; Sood, S. (Inderscience Enterprises Ltd, 2015)
The study here probes the perspective that consumers use certain brands as actors that play roles in the consumers’ lives and that help consumers as protagonists to enact roles that give them the feelings of achievement, well-being, and/or emotional excitement. The method enables the uncovering of archetypes as unconscious forces that drive consumers to specific actions implicitly and to a less extent, explicitly. The study employs two techniques: degrees-of-freedom analysis (DFA) to test whether or not consumer stories fit a given archetypal theme and visual narrative art (VNA) to confirm whether or not consumer’s own stories enact a specific archetype and how such enactments are done. This study offers an alternative for survey auditing consumer-brand relationships; the study here describes and explains the importance of narratives in consumer behaviour and the use of archetypes as universal themes that aid understanding of brand-consumer relationships. The study describes DFA and VNA with two examples of the use of these analytics.